Morphological characterization of permanent dentition of a group of Afrodescendants at Istmina (Chocó, Colombia) - Asprilla, Pedro; Franco, Kevin; Morales, Jessica; Moreno, Freddy (Revista Estomatología, 2017)
Aim: Characterize the permanent dentition morphology of a group of Afrodescendants of Istmina (Chocó, Colombia). Materials y methods: This quantitative cross-sectional study determined the frequency and variability of 35 incisor, canine, premolar and molar morphological features of the Arizona State University Dental Anthropology System in 100 self-described individuals as Afrodescendants (50 Female and 50 male), aged between 5 and 18 years. Results: Significant frequencies of winging (99%), double blade of the central incisors (86%), convexity of the lips (41%), crest of the shoulder (35%), and distal crest (39% to 45%) were identified (95% to 98%), central ridge (82% and 80%), mesolingual groove (79%), distolingual groove (81%), hippocampus reduction (86%), Carabelli cusp ) And cusp 7 (64%). No sexual dimorphism and bilateral asymmetry were found in the MCDS studied. Conclusions: The frequency and variability of the MCDD included in the dendrogram showed that the Isthmian group had a typical dental morphology of the Afrodescendant populations distributed on the Colombian Pacific coast, which were derived from groups of the West African coast included in The dental complex of Saharan Africa. Likewise, it was possible to detect the influence of mestizo and indigenous populations occupying the same geopolitical space.